PENGENALAN APLIKASI HADIS ‘SATU HARI SATU HADIS” DAN “40 HADIS MUDAH DIHAFAL” - Muhammad Arfan Muhammad Arfan; Adam Firdaus Adam Firdaus (AL-ATSAR: Jurnal Ilmu Hadits, 2023)
This article discusses two digital applications that help in the dissemination and learning of hadith by taking Satu Hari Satu Hadis and 40 Hadis Mudah Dihafal applications as samples. This research is motivated by the development of learning facilities in the era of advances in information technology, which can be seen by digitization various of learning media. Facts in the field have proven that in the past hadith were learned directly from competent teachers. But along with the times, especially in this digitization era, people are more likely to like technology-based learning. From this issue it is necessary to discuss applications that aim to spread and learn digital-based hadith, namely the Satu Hari Satu Hadis application and the 40 Hadis Mudah Dihafal Application. This research is an applied research, with the data collection technique used is to try the application directly. From this research, it can be found that these two applications are very practical to use for learning hadith and memorizing it. The digitization of hadith learning will make learning hadith process easier to be accessed and studied by various groups in various situations practically.